Two new species of the genus Arrenurus from Pohnpei, Federal States of Micronesia (Acari: Hydrachnidia: Arrenuridae) - Smit, Harry (Zootaxa, 2010)
Two new species of the genus Arrenurus, A. cornuatus and A. kostkai are described from high elevation, head water streams on the island of Pohnpei, Micronesia.